YOUNG WOMEN’S INVESTMENT DECISIONS: BEHAVIORAL BIASES AND FINANCIAL LITERACY - Zuwina Miraza; Hafriz Rifki Hafas; Listiorini; Mutiah Fitriani; Miftahul Rizqina (Insan Doktor Ekonomi Indonesia (IDEI), 2026)
This quantitative study analyzed the influence of behavioral biases (overconfidence, representativeness, anchoring, and availability) on investment decision-making, with financial literacy as a mediating variable. The sample used 200 female investor respondents in North Sumatra, selected through purposive sampling. Primary data were obtained through a questionnaire distributed via Google Forms and analyzed using the SEM-PLS method with SmartPLS 4 software. The results showed that only representativeness bias had a significant effect on investment decisions. Meanwhile, overconfidence bias, anchoring bias, and availability bias had no significant effect. Another important finding was that financial literacy did not mediate the relationship between behavioral biases and investment decision-making and did not have a significant direct effect on investment decisions. The conclusion of this study is that representativeness bias is a dominant factor in investment decision-making among respondents, while the mediating role of financial literacy is not significant.